2010
DOI: 10.1111/j.1743-6109.2009.01642.x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Muscle Assessment Outcomes in Women With and Without Provoked Vestibulodynia and the Impact of a Physical Therapy Program

Abstract: Introduction Physical therapy (PT) may reduce the pain associated with provoked vestibulodynia (PVD) based on previous findings that pelvic floor muscle dysfunction (PFMD) is associated with PVD symptoms. Aims The goals of this study were: (i) to determine whether women with and without PVD differ on measures of pelvic floor muscle (PFM) behavior; and (ii) to assess the impact of PT treatment for women with PVD on these measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 70 publications
(140 reference statements)
7
136
3
3
Order By: Relevance
“…This study found no significant differences between women with and women without PVD in VRP, PFM strength or endurance, while the present study found a significant difference in VRP. Elevated VRP might be maintained passively due to inelasticity of vaginal soft tissue [10]. In the study by Polpeta et al [26] the control group had a higher VRP than the PVD group, whereas sEMG resting activity was slightly higher in the vulvodynia group, which is contrary to our findings.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This study found no significant differences between women with and women without PVD in VRP, PFM strength or endurance, while the present study found a significant difference in VRP. Elevated VRP might be maintained passively due to inelasticity of vaginal soft tissue [10]. In the study by Polpeta et al [26] the control group had a higher VRP than the PVD group, whereas sEMG resting activity was slightly higher in the vulvodynia group, which is contrary to our findings.…”
Section: Discussioncontrasting
confidence: 56%
“…More specifically vaginal overactivity, lack of pelvic floor muscle strength and "restriction of the vaginal opening" have been hypothesized to be associated with PVD [8;9], but there are few studies assessing these variables in women with PVD compared to controls [10], and the reported findings on overactivity of the PFM are contradictory [9][10][11][12]. The reliability and validity of digital palpation of the PFM has been questioned [13], and vaginal surface EMG (sEMG) recordings may be flawed by cross-talk activity from other muscles.…”
mentioning
confidence: 99%
“…A first retrospective study investigating such a program in a sample of 35 women diagnosed with PVD yielded a 52 % success rate with regard to pain reduction and a significant improvement in participants' sexual functioning [107]. Using a prospective methodology, another study in a sample of 11 women diagnosed with PVD, Gentilcore-Saulnier et al [108] demonstrated that a physical therapy program led to the normalization of the pelvic floor. Women also reported a significant reduction in pain during vaginal palpation and significant decreases in pain during intercourse and during a gynecological examination, as well as improved sexual function [109].…”
Section: Physical Therapy Treatmentsmentioning
confidence: 95%
“…Proposed biomedical factors include vaginal infections [7], genetic or immune factors [8], hormonal factors [9], or the proliferation of nociceptors and sensitization [10]. Pelvic floor muscle (PFM) dysfunctions may also play an important role [11], [12] and [13]. It has been reported that women with PVD have heightened PFM tone as well as inferior PFM strength, coordination and endurance compared to asymptomatic women [11], [12] and [13].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic floor muscle (PFM) dysfunctions may also play an important role [11], [12] and [13]. It has been reported that women with PVD have heightened PFM tone as well as inferior PFM strength, coordination and endurance compared to asymptomatic women [11], [12] and [13]. Targeting these dysfunctions, multimodal physiotherapy treatment includes education, biofeedback, manual and insertion techniques [14].…”
Section: Introductionmentioning
confidence: 99%